Does computer use pose an occupational hazard for forearm pain; from the NUDATA study. Issue 11 (22nd October 2003) - Kryger, A I; Andersen, J H; Lassen, C F; Brandt, L P A; Vilstrup, I; Overgaard, E; Thomsen, J F; Mikkelsen, S
Abstract : Aims: To determine the occurrence of pain conditions and disorders in the forearm and to evaluate risk factors for forearm pain in a cohort of computer workers. Methods: A total of 6943 participants with a wide range of computer use and work tasks were studied. At baseline and at one year follow up participants completed a questionnaire. Participants with relevant forearm symptoms were offered a clinical examination. Symptom cases and clinical cases were defined on the basis of self reported pain score and palpation tenderness in the muscles of the forearm. Results: The seven days prevalence of moderate to severe forearm pain was 4.3%. Sixteen of 296 symptom cases met criteria for being a clinical forearm case, and 12 had signs of potential nerve entrapment. One year incidence of reported symptom cases was 1.3%; no subjects developed new signs of nerve entrapment. Increased risk of new forearm pain was associated with use of a mouse device for more than 30 hours per week, and with keyboard use more than 15 hours per week. High job demands and time pressure at baseline were risk factors for onset of forearm pain; women had a twofold increased risk of developing forearm pain. Self reported ergonomic workplace factors at baseline did not predict future forearm pain. Conclusion: Intensive use of a mouse device, and to a lesser extent keyboard usage, were the main risk factors for forearm pain. The occurrence of clinical disorders was low, suggesting that computer use is not commonly associated with any severe occupational hazard to the forearm.